Intratumoral cancer chemotherapy with a carrier-based immunogenic cell death eliciting platinum (IV) agent - Groer, Chad (Mol Pharm, 2020)
A carrier-based, immunogenic cell death (ICD)-eliciting platinum(IV) chemotherapeutic agent was synthesized via complexation between an axially derivatized Pt(IV)-tocopherol and hyaluronan-tocopherol nanocarrier. The resultant HA-Pt(IV) complex demonstrated anti-proliferative activity and induced calreticulin translocation, an indicator of ICD, in murine and human head and neck cancer cells. The intratumorally administered HA-Pt(IV) treatments were tolerable and efficacious in both immunocompetent and immunodeficient mice with head and neck cancer, partially due to the direct cytotoxicity. Superior efficacy and survival was observed in the immunocompetent group, suggesting a possible Pt(IV)-induced immunological response, which would only manifest in animals with an intact immune system. Subsequent imaging of tumor tissues demonstrated increased macrophage infiltration in the HA-Pt(IV) treated tumors compared to the non-treated controls and the cisplatin-treated tumors, suggesting favorable inflammatory activation. RNA sequencing of HA-Pt(IV)-treated tumors indicated that carbohydrate and vitamin metabolisms were the most important Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and molecular function, biological process and cellular component were highly enriched gene ontology (GO) categories.